KEMITRAAN BUMN DENGAN UKM SEKTOR INDUSTRI DI KABUPATEN SLEMAN: ANALISIS MODEL BALANCE SCORECARD - Gendro Wiyono (JURNAL MANAJEMEN, 2014)
The research was conducted to determine the effect on the performance of SOEs Partnership Program SMEs in Sleman, Yogyakarta Special Region, using the balance scorecard approach to performance evaluation. In assessing the implementation of the coaching process, researchers use a measure of the principles of the new paradigm of Osborne and Gaebler (Tamba, 2004), while to know the direction of marketing strategies using the concept of Kotler and Armstrong (1989). The results showed that the implementation is not in accordance with the spirit of partnership that mandated by the rules. Working Capital Loans are given relatively small, and Investment Assistance Loans are only given to 10 SMEs (27.78%). Fostering human resources in the form of education and apprenticeship is never done, while the training is only carried out on eight SME (22.22%). In addition, the Marketing and Promotion Development aid is only granted to 12 SMEs (33.33%). The value of loans granted though relatively small, but was still significant (0.675; t-stat = 2.069) on shareholder value, this is because the loans are disbursed only to micro-businesses that had little effect so the increase that occurred has no positive value for welfare of society at large. Coaching HR does not provide a significant positive effect, even a negative effect on organizational capital (-0.465; t-stat=6.658) and no effect also on human capital (0.000). Similarly, the Business Development also no significant effect on shareholder value (-0.435; t-stat= 1.145) but significant positive effect on human capital (0.877; t-stat=17.417). Furthermore, the findings based on the principles of the new paradigm suggests that the implementation of the coaching was done SOE Partners Equity Loans weakened the influence of shareholder value (0.241; t-stat=1.498), whereas the implementation of the Referral Marketing Strategy Business Development to strengthen the influence of shareholder value (0.781; t-stat=4.252). Finally it can be concluded that the Capital Loan significant positive effect on shareholder value but does not give effect to the wider community. Positive and significant influence of human capital to organizational capital and equity firms occurred not due to the results of state-owned development partners, but tend to be because SMEs itself in terms of relationship and managerial capabilities.